Organizational measurement of defect density - Hasim, Nurdatillah (2009)
Measurement and Analysis Process is one of process areas covered in the Capability Maturity Model Integration (CMMI) Level 2. However, in order to produce the measurement a proper plan and process are required. Organizational Measurement of Defect Density is a measurement conducted in HeiTech Padu Berhad (HeiTech). This project report will be discussing the issue of defect density measurement focusing on defects found during testing phase. Issue raised with defect density measurement is that the result of the measurement tends to be imprecise because of the various ways used to count the line of codes. To this end, this project report presents a method for measurement process in order to calculate defect density which is the HeiTech Measurement and Analysis Process. These methods consist of three phases which are Planning, Implementing and Improving phase. As for the implementation, three projects has been selected which are BHEUU-CSMBBG, BHEUU-SKHD and iProcurement-Vendor Management. Line of code for all three projects has been count using selected code counter which is GeroneSoft Code Counter Pro V1.32. Moreover, along with the defect classification developed it has been useful and effective in turn to detect defect discover in a program. As for defect density measurement output, results has been gathered and presented in the Measurement and Analysis Report.